Uncompromising Positions: Reiterations of Misogyny Embedded in Lesbian and Feminist Communities' Framing of Lesbian Femme Identities - Stafford, Anika (Atlantis)

(untitled) (Mount Saint Vincent University, 2010)
Queer femmes in 1950s bar cultures were often not viewed as "real lesbians;" radical feminism condemned femmes as trying to please patriarchy. This paper investigates ways such views regarding femmes reiterate misogynist notions of female bodies. It places femme narratives challenging such conceptualizations as contesting counter-cultural reiterations of misogyny.